EFFECT OF HERDING BIAS, OVERCONFIDENCE BIAS AND DISPOSITION BIAS IN INVESTMENT DECISIONS: A STUDY OF INDIVIDUAL INVESTORS IN THE SEMARANG CAPITAL MARKET COMMUNITY - Adam Ma’rifat Muslim; Andi Wijayanto; Dinalestari Purbawati (Universitas Diponegoro, 2026)
Abstract: This paper focuses on doing explanatory research using a quantitative approach. Specialised in basic linear regression analysis, the investigation was carried out using SPSS 27 Version for Mac software. It may be concluded that the Disposition Bias variable has a positive impact on the investment decision variable. This study examines the beneficial impact of the overconfidence bias variable on the investment decision variable. Furthermore, the variable of investment decision is favourably influenced by the variable of herding bias. Based on these results, the suggestions that can be conveyed by researchers, namely to individual investors who are members of the capital market community in Semarang. To further improve understanding of the capital market and financial planning. It is hoped that investors can be alert to irrational behaviors, thus enabling investors to make more rational and planned decisions.Keywords: Behavioural Finance; Stock; Investment Decision; Investor